Sustainability of dairy farming in Colombia’s High Andean region - Durana, Claudia; Murgueitio, Enrique; Murgueitio, Bernardo (Frontiers in Sustainable Food Systems, 2023)
Bovine livestock occupies more than a third of the earth's surface and has been responsible for the transformation of various natural ecosystems in different parts of the world, including those that occupy fragile, biodiverse regions. Such livestock is found in several of these types of regions throughout Colombia, which are faced with productivity limitations and environmental impacts. The Andean highlands region represents a strategic ecosystem for the conservation of biodiversity at a global level and contains a variety of ecosystems on different scales. Dairy farming in this region has undeniable socioeconomic relevance that is currently threatened by climate variability and the market globalization. Key elements for the sustainability of livestock in the Andean highland region are explored, considering environmental conditions, its technical and economic viability, as well as its relationship with the values and objectives of society. The factors that hinder dairy farming in the Andean highland region are analyzed through applied research, field trials, participant observation with production groups, consultation with experts, and bibliographic reviews, as well as comparisons of natural resources’ vulnerability against conventional production models from the perspective of sustainability. Sustainability-seeking alternatives are identified, such as agroecological intensification in silvopastoral systems integrated with biodiversity conservation tools whose implementation can generate the formation of multifunctional landscapes.